2007
DOI: 10.1111/j.1750-3639.2007.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Behavioral Assays Relevant to the Symptoms of Autism*

Abstract: While the cause of autism remains unknown, the high concordance between monozygotic twins supports a strong genetic component. The importance of genetic factors in autism encourages the development of mutant mouse models, to advance our understanding of biological mechanisms underlying autistic behaviors. Mouse models of human neuropsychiatric diseases are designed to optimize (i) face validity (resemblance to the human symptoms) (ii) construct validity (similarity to the underlying causes of the disease) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
444
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 505 publications
(454 citation statements)
references
References 208 publications
(317 reference statements)
6
444
0
4
Order By: Relevance
“…Isolation-induced ultrasonic vocalizations (USVs) are an infantmother vocal communicative behavior that is thought to be relevant to autism (14,20). We found that Prex1 −/− pups emitted significantly fewer ultrasonic calls than did WT littermates (Fig.…”
Section: Significancementioning
confidence: 78%
“…Isolation-induced ultrasonic vocalizations (USVs) are an infantmother vocal communicative behavior that is thought to be relevant to autism (14,20). We found that Prex1 −/− pups emitted significantly fewer ultrasonic calls than did WT littermates (Fig.…”
Section: Significancementioning
confidence: 78%
“…On the background of this apparent normality, the three major behavioral impairments that we observed are remarkable. (i) We detected a large increase in repetitive grooming behaviors, indicating an abnormality with face validity to one of the three major symptom domains relevant to autism (31,40). (ii) We measured a decrease in PPI, suggesting impaired sensorimotor gating.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation-induced USVs are inherently social (Hofer et al, 2002;Harmon et al, 2008), and reductions of USVs have been found in rodent models of ASDs (Crawley, 2007;Higashida et al, 2011). Diminished USVs in rat pups are suggested to model the lack of crying observed in some children with ASDs (Crawley, 2007). The early deficit in USV production may therefore reflect social dysfunction that persists into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The pitch of USVs from control pups decreased with age, as previously reported (Kromkhun et al, 2013), but increased with age in PS pups, further suggesting atypical development following PS. Isolation-induced USVs are inherently social (Hofer et al, 2002;Harmon et al, 2008), and reductions of USVs have been found in rodent models of ASDs (Crawley, 2007;Higashida et al, 2011). Diminished USVs in rat pups are suggested to model the lack of crying observed in some children with ASDs (Crawley, 2007).…”
Section: Discussionmentioning
confidence: 99%